Qos in Parallelized E-Commerce Systems - Diniz, Bruno; Pereira, Rodrigo; Meira Jr., Wagner; Almeida, Virgílio (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41219, 2000)
The proliferation and variety of e-commerce services makes the maintenance of the quality of the services (QoS) provided an essential feature for successful sites. In this paper we propose an application-level strategy for differentiating e-commerce services that is based on variating the number of threads employed for satisfying a request. In order to validate and evaluate our strategy, we implemented an ad server that provides two levels of service. For sake of service differentiation, our strategy showed to be effective, allowing high-priority requests to be answered up to 60% faster than low-priority requests, although the differentiation reduces as the workload that is submitted to the server increases.